Preparation of cation-exchange membrane chromatography through modification of polyamide membrane by grafting of acrylic acid monomer - Nur Aishah Amalin, Ramjis (2012)
Packed bed chromatography is widely used for protein separation and purification.However some limitation of packed bed chromatography has been identified such as high-pressure drop,internal diffusion limitation and compaction for the soft beads.This encourages people to use membrane chromatography as alternative to the packed bed chromatography.In this study,membrane chromatography was developed from polyamide-based membrane by grafting acrylic acid (AA) monomer to produce cation-exchanger membrane chromatography.During grafting process,the concentration of AA monomer from 0.1 M to 1.0 M and grafting time from 15 min to 120 min was studied.The optimum monomer concentration was achieved at 0.5 M with a binding capacity of 443.39 mg BSA/g membrane.The optimum reaction time is 45 minutes which gives a binding capacity of 533.40 BSA mg/g membranes.The BSA adsorption capacity can be related to the amount of carboxyl group present in the modified membrane surface after grafting process.The successful of membrane chromatography preparation depend on the careful optimization the chemical reaction parameters involve.